Bacterial infection during wars, conflicts and post-natural disasters in Asia and the Middle East: a narrative review. Issue 6 (2nd June 2020) - Nawfal Dagher, Tania; Al-Bayssari, Charbel; Diene, Seydina M.; Azar, Eid; Rolain, Jean-Marc
ABSTRACT: Introduction: Bacterial infections resulting from wars and natural disasters represent a major public health problem. Over the past 50 years, Asia and the Middle East have suffered several wars. Moreover, East-Asian countries are considered the most natural disaster-prone countries in the world. Areas covered: This review focuses on bacterial infection occurring during wars and after natural disasters, among refugees, wounded citizens and soldiers as well as the prevention and control measures that must be taken. Expert opinion: During wars, refugees and soldiers represent the two main sources of bacterial infections. Refugees coming from countries with a high prevalence of antimicrobial resistance can spread these pathogens to their final destination. In addition, these refugees living in inadequate shelters can contribute to the spread of bacterial infections. Moreover, some factors including the presence of fixed imported fragments; environmental contamination and nosocomial transmissions, play a key role in the dissemination of bacteria among soldiers. As for natural disasters, several factors are associated with increased bacterial transmissions such as the displacement of large numbers of people into over-crowded shelters, high exposure to disease vectors, lack of water and sanitation. Here, we carry out a systematic review of the bacterial infections that follow these two phenomena.